PENERAPAN LAYOUT DENGAN METODE SYSTEMATIC LAYOUT PLANNING DALAM MENINGKATKAN KELANCARAN PRODUKSI PADA UD.TEMON RAYA KABUPATEN PACITAN - Disworo Prayogo Utomo; Setyo Adji; Dwi Warni Wahyuningsih (Bussman Journal : Indonesian Journal of Business and Management, 2022)
The purpose of this research is to determine the layout of the production facilities implemented by UD Temon Raya Pacitan Regency, and then Relayout is performed using the Systematic Layout Planning (SLP) method. This study employs descriptive quantitative methods or descriptive survey research, with data obtained through observations, documentation, and interviews with parties who understand the data required. Based on the results of UD's initial Layout effectiveness test. Temon Raya has a 29.9 % application effectiveness value, with a daily production capacity of 200 pcs and 11 main work stations. While the layout of the design results using the Systematic Layout Planning method has an application effectiveness value of 45.45 %, with the same production capacity and number of work stations, the redesign of the layout of production facilities using the Systematic Layout Planning (SLP) method will be able to improve the smoothness of the process. As a result, the layout design created using the Systematic Layout Planning (SLP) method can be used as a starting point for redesigning the layout of UD's manufacturing facilities. Pacitan Raya Regency Temon Raya